Overview of available p53 function tests in relation to TP53 and ATM gene alterations and chemoresistance in chronic lymphocytic leukemia - Raa, G. Doreen te; Malcikova, Jitka; Pospisilova, Sarka; Trbusek, Martin; Mraz, Mark; Garff-Tavernier, Maria Le; Merle-Béral, Hélène; Lin, Ke; Pettitt, Andrew R.; Merkel, Olaf; Stankovic, Tatjana; van Oers, Marinus H.; et al. (Leukemia and lymphoma, 2013)
The ATM-p53 DNA damage response pathway plays a crucial role in chemoresistance in chronic lymphocytic leukemia, as indicated by the adverse prognostic impact of deletions of 17p (locus of TP53) and 11q (locus of ATM) detected by fluorescence in situ hybridization (FISH) analysis. In addition to deletions, mutations in these respective genes are also associated with chemoresistance, and add to the prognostic information provided by FISH. In order to explore the possibility that dysfunction of the ATM-p53 pathway might also result from mechanisms other than ATM/TP53 deletion/mutation, assays have been developed that probe the functional integrity of the ATM-p53 pathway. Currently, four different p53 function assays have been developed that are based on the measurement of p53 and p53-dependent genes at the RNA (real-time polymerase chain reaction [RT-PCR]p21; RT-PCRmiR34a; reverse transcription-multiplex ligation-dependent probe amplification assay [RT-MLPA]p21, bax, puma and CD95) or protein (fluorescence activated cell sorting [FACS]p53-p21) level in untreated cells or following irradiation or drug treatment. Here we provide an overview of these assays based on the available literature.